Is there a Safe Level of Alcohol that can be consumed during Pregnancy without causing Adverse Outcomes to the Child and is this being communicated effectively to Pregnant Women? - Fairbrother, Louise (2008)
Introduction The research question for the dissertation was ÃÂIs there a safe level of alcohol that can be consumed during pregnancy without causing adverse outcomes to the child and is this being communicated effectively to pregnant women?" To answer the question the dissertation was carried out in the form of a literature review and examined research carried out into the effects of differing levels of prenatal alcohol exposure to the foetus. The guidelines created in England and other countries with regard to alcohol use during pregnancy and the published information being provided to women during their pregnancy were also examined.